QSAR modeling of benzoquinone derivatives as 5-lipoxygenase inhibitors - T.K. Shameera Ahamed; Vijisha K. Rajan; K. Muraleedharan (Food Science and Human Wellness)
The inhibitors of 5-LOX control the overproduction of pro-inflammatory mediators known as leukotrienes (LTs) and thus have therapeutic relevance in the treatment of various diseases like asthma, rheumatoid arthritis, inflammatory bowel disease and certain types of cancers. This has increased the search for efficient therapeutic agents for protein 5-LOX and this process is now primarily based on QSAR. In this study, we have developed four different quantitative structure and 5-LOX inhibition activity relationship models of benzoquinone derivative by exploiting CoMFA, RF, SVM, and MLR chemometric methods. Performance of the QSAR models was measured by using cross-validation technique as well as through the external test set prediction. RF model outperforms all other models. SVM and MLR models failed due to the poor performance of the external test set prediction. CoMFA model, which shows relatively good performance was used to explore the essential structural regions where the modification was necessary to design a novel scaffold with improved activity. Moreover, molecular docking of all the derivatives to the binding site of 5-LOX was done to show their binding mode and to identify critical interacting residues inside the active site of 5-LOX. The docking result confirms the stability and rationality of the CoMFA model. Keywords: 5-lipoxygenase, Benzoquinone, 2D-QSAR, 3D-QSAR, Molecular docking